2010
DOI: 10.1167/iovs.09-4505
|View full text |Cite
|
Sign up to set email alerts
|

Differential Distribution of Blood and Lymphatic Vessels in the Murine Cornea

Abstract: Blood and lymphatic vessels are not evenly distributed in normal limbal areas. Furthermore, corneal LG and HG respond differently to inflammatory stimuli. These new findings will shed some light on corneal physiology and pathogenesis and on the development of experimental models and therapeutic strategies for corneal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 28 publications
1
53
1
Order By: Relevance
“…A study that induced corneal neovascularization in rats using sutures showed an initial growth of both blood and lymphatic vessels following a temporary inflammatory insult to the cornea, although lymphatics regressed earlier than blood vessels (27) . Ecoiffier et al also used sutureinduced inflammation to demonstrate different lymphangiogenic and haemangiogenic responses to an inflammatory stimulus, correlating these findings with others that show different regression periods (34) . As regards changes found near lymphatic vessels (Chart 5), myofibroblasts and anterior synechiae were present in a large number of specimens, having been observed in 23 (22.11%) and 15 cases (14.42%), respectively.…”
Section: Discussionmentioning
confidence: 59%
“…A study that induced corneal neovascularization in rats using sutures showed an initial growth of both blood and lymphatic vessels following a temporary inflammatory insult to the cornea, although lymphatics regressed earlier than blood vessels (27) . Ecoiffier et al also used sutureinduced inflammation to demonstrate different lymphangiogenic and haemangiogenic responses to an inflammatory stimulus, correlating these findings with others that show different regression periods (34) . As regards changes found near lymphatic vessels (Chart 5), myofibroblasts and anterior synechiae were present in a large number of specimens, having been observed in 23 (22.11%) and 15 cases (14.42%), respectively.…”
Section: Discussionmentioning
confidence: 59%
“…It enables the epithelial cells to interact with ECM and chemical signals diffused from the vascular network [110] . Some studies showed that the limbus has a specific anatomic structure such as the niche, the LEC (limbal epithelial crypt) or LC (limbal crypt), which consists of a cord or finger of cells that are located between the palisades of the limbal stroma and extends radically to the conjunctiva stroma [92,93] .…”
Section: Stem Cells In Ocular Tissuesmentioning
confidence: 99%
“…[21][22][23][24] Briefly, freshly excised corneas were fixed in acetone for immunofluorescent staining. Nonspecific staining was blocked with anti-Fc CD16/CD32 antibody (BD Biosciences, San Jose, CA) and donkey serum ( Jackson ImmunoResearch Laboratories Inc. West Grove, PA).…”
Section: Immunofluorescent Microscopic Assaymentioning
confidence: 99%
“…[21][22][23][24][25] Basically, vessels in each sample were evaluated using 4 parameters: invasion area, density, diameter, and branching points. The invasion area was presented in a percentage coverage score obtained by normalizing the vascular area to the total corneal area.…”
Section: Vascular and Macrophage Quantificationmentioning
confidence: 99%